2019
DOI: 10.1016/j.ptsp.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic strength differences between elite senior and youth female soccer players identifies training requirements

Abstract: Objectives: To compare traditional and angle-specific isokinetic strength of eccentric knee flexors and concentric knee extensors in female senior professional and youth soccer players. Design: Crosssectional study design. Setting: University's Laboratory. Participants: A total of 34 players (17 seniors [age 25.31 ± 4.51 years; height 167.89 ± 7.04cm; mass 63.12 ± 7.79kg] and 17 youths [16.91 ± 1.16 years; height 165.92 ± 4.42cm; mass 60.07 ± 4.48kg]) from the Women's Super League 1 completed strength assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…In contrast, eccKF peak torque is maintained with increasing velocity, and therefore as angular velocity increased the quadriceps dominance apparent at slow velocities was reduced. The conKE and eccKF torque-velocity curves did not cross as observed by Eustace et al (2019) in senior professional players, where the eccentric knee flexors became dominant at velocities greater than approximately 200°•s −1 . This might reflect the relative training status of the samples, with the youth players used in the current study not generating the same magnitude of peak torques observed by Eustace et al (2017).…”
Section: Practical Implications For Isokinetic Data Collectionmentioning
confidence: 46%
“…In contrast, eccKF peak torque is maintained with increasing velocity, and therefore as angular velocity increased the quadriceps dominance apparent at slow velocities was reduced. The conKE and eccKF torque-velocity curves did not cross as observed by Eustace et al (2019) in senior professional players, where the eccentric knee flexors became dominant at velocities greater than approximately 200°•s −1 . This might reflect the relative training status of the samples, with the youth players used in the current study not generating the same magnitude of peak torques observed by Eustace et al (2017).…”
Section: Practical Implications For Isokinetic Data Collectionmentioning
confidence: 46%
“…Age-related differences within isokinetic strength of elite youth football players' lower limbs were evaluated in many studies (Kellis et al;Forbes et al, 2009;Lehnert et al, 2011;Bona et al, 2017;Eustace et al, 2019;Zahalka et al, 2019). In summary, part of the studies reported a significant effect of age on isokinetic strength of players; however, another part of the findings is inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had shown different results where there were differences in sprint performance based on playing positions and there was no difference in sprint performance based on the age category (Haugen et al, 2012). Previous studies had suggested that sprint performance and high-intensity running distance observed in senior female soccer players were better than in young players (Eustace et al, 2019). Other studies revealed that there was no comparison of aerobic and anaerobic capacity parameters between adult and young elite soccer players (Angius et al, 2012).…”
Section: Discussionmentioning
confidence: 96%